Establishment of a primary renal lymphoma model and its clinical relevance - Li, Xiaoxi; Deng, Minyao; Zhang, Chenxiao; Luo, Lingli; Qian, Hui (Frontiers in Oncology, 2023)
Extranodal dissemination is an important feature of aggressive B-cell lymphoma. Due to the lack of available animal models, the study on extranodal dissemination of lymphoma is greatly limited. Here, we identified a novel cell line, named MA-K, which originated from the Eμ-Myc;Cdkn2a-/- cell line, named MA-LN in this study. Compared to MA-LN, MA-K tended to disseminate in the kidney rather than lymph nodes in lymphoma transplantation model, resembling human primary renal lymphoma. The transcriptome analysis revealed that MA-K had undergone the transcriptional evolution during the culture. Specialized transcriptional pattern analysis, we proposed in this study, identified that FOXO1-BTG1-MYD88 pattern was formed in MA-K. Further analysis found that translation pathway was the most enriched pathway in specially expressed genes (SEGs) in MA-K. Among the SEGs, 3 up-regulated genes, RPLP2, RPS16 and MRPS16, and 5 down-regulated genes, SSPN, CD52, ANKRD37, CCDC82 and VPREB3, in MA-K were identified as promising biomarkers to predict the clinical outcomes of human DLBCL. Moreover, the joint expression of the 5-gene signature could effectively predict clinical outcomes of human DLBCL in triple groups. These findings suggested that the MA-K cell line had strong clinical relevance with human aggressive B-cell lymphoma. Moreover, the MA-K primary renal lymphoma model, as a novel syngenetic mouse model, will be greatly useful for both the basic research on lymphoma dissemination and preclinical efficacy evaluation of chemotherapy and immunotherapy.